2014
DOI: 10.1039/c4ta04439h
|View full text |Cite
|
Sign up to set email alerts
|

Ternary composites of delaminated-MnO2/PDDA/functionalized-CNOs for high-capacity supercapacitor electrodes

Abstract: Synthesis via sequential deposition of polydiallyldimethylammonium chloride (PDDA), delaminated-manganese oxide (MnO2) and functionalized carbon nano-onions (ONCNOs) produces high-performance supercapacitor electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Among the materials like manganese oxide, ruthenium oxide, nickel hydroxide, PANI, polypyrrole (PPy), etc, the manganese oxide/carbon onion composite showed the maximum specific capacitance of 575 F g −1 in 0.5 M H 2 SO 4 electrolyte [ 121 ]. Borgohain et al [ 122 ] reported the polydiallyldimethylammonium chloride (PDDA) modified carbon nano-onion with MnO 2 (55 wt%) symmetric cell, which delivered a maximum capacitance of 218 F g −1 in liquid electrolyte with a high energy density of 6.14 Wh kg −1 . Wang et al [ 123 ] reported the (MnO 2 )/onion-like carbon (OLC)-based nanocomposite electrode with the specific capacitance of 177.5 F g −1 .…”
Section: Non-faradaic Capacitive (Edlc Type) Electrode Materialsmentioning
confidence: 99%
“…Among the materials like manganese oxide, ruthenium oxide, nickel hydroxide, PANI, polypyrrole (PPy), etc, the manganese oxide/carbon onion composite showed the maximum specific capacitance of 575 F g −1 in 0.5 M H 2 SO 4 electrolyte [ 121 ]. Borgohain et al [ 122 ] reported the polydiallyldimethylammonium chloride (PDDA) modified carbon nano-onion with MnO 2 (55 wt%) symmetric cell, which delivered a maximum capacitance of 218 F g −1 in liquid electrolyte with a high energy density of 6.14 Wh kg −1 . Wang et al [ 123 ] reported the (MnO 2 )/onion-like carbon (OLC)-based nanocomposite electrode with the specific capacitance of 177.5 F g −1 .…”
Section: Non-faradaic Capacitive (Edlc Type) Electrode Materialsmentioning
confidence: 99%
“…For instance, incorporation of the third component, say, graphene or conducting polymer or CNTs component to MnO 2 (first component) and conducting polymer or graphene system or porous nanocarbons (second component) have markedly upgraded the overall capacitance and cyclic stability through modifications in the electrical conductivity, contact interactions, porosity, electrochemical surface activities besides improving the mechanical flexibility, etc. of the resultant ternary nanocomposite electrodes relative to the corresponding MnO 2 /conducting polymer or MnO 2 /graphene or MnO 2 /CNTs binary electrode systems respectively [161–212] …”
Section: Electrochemical Performances Of Various Mno2‐based Ternary Nmentioning
confidence: 99%
“…S4, ESI †), demonstrating its superior cycling stability. Compared to manganese oxide based electrode materials recently reported for supercapacitors (Table S1, ESI †), [24][25][26]28,29,41,42,45,[58][59][60] the as-photodeposited 3D hierarchical Mn 3 O 4 /H-TiO 2 composite film electrode shows larger specific capacitances at higher current rates and markedly enhanced electrochemical cycling stability, which can be attributed to its unique structure characteristics. The hierarchical architecture can provide easy access of the surfaces to the liquid electrolyte, thus providing more active sites for the pseudocapacitive reactions.…”
Section: Capacitance Performancementioning
confidence: 99%